(untitled) (Academia Science Repository, 2023)
Over the past decades, the problem of euphemization speech was constantly in the focus of attention of researchers in Europe and America, as evidenced by numerous dictionaries euphemisms of the English language, published in the USA and Great Britain. Various aspects of euphemia are currently being found in the studies of Uzbek linguists as well.